On-Demand Cell Sheet Release with Low Density Peptide-Functionalized Non-LCST Polymer Brushes - Schulte, Anna; de Los Santos Pereira, Andres; Pola, Robert; Pop-Georgievski, Ognen; Jiang, Siyu; Romanenko, Iryna; Singh, Manisha; Sedláková, Zdeňka; Schönherr, Holger; Poręba, Rafał (Macromolecular bioscience, 2023)
Cell sheet harvesting offers a great potential for the development of new therapies for regenerative medicine. For cells to adhere onto surfaces, proliferate, and to be released on demand, thermoresponsive polymeric coatings are generally considered to be required. Herein, an alternative approach for the cell sheet harvesting and rapid release on demand is reported, circumventing the use of thermoresponsive materials. This approach is based on the end-group biofunctionalization of non-thermoresponsive and antifouling poly(2-hydroxyethyl methacrylate) (p(HEMA)) brushes with cell-adhesive peptide motifs. While the nonfunctionalized p(HEMA) surfaces are cell-repellant, ligation of cell-signaling ligand enables extensive attachment and proliferation of NIH 3T3 fibroblasts until the formation of a confluent cell layer. Remarkably, the formed cell sheets can be released from the surfaces by gentle rinsing with cell-culture medium. The release of the cells is found to be facilitated by low surface density of cell-adhesive peptides, as confirmed by X-ray photoelectron spectroscopy. Additionally, the developed system affords possibility for repeated cell seeding, proliferation, and release on previously used substrates without any additional pretreatment steps. This new approach represents an alternative to thermally triggered cell-sheet harvesting platforms, offering possibility of capture and proliferation of various rare cell lines via appropriate selection of the cell-adhesive ligand.
Keywords: polymery; povrchové vlastnosti; Ligands; buněčná adheze; Polymers; peptidy; Cell Adhesion; Surface Properties; Peptides; ligandy